A preliminary survey on the religious profile of Brazilian psychiatrists and their approach to patients' religiosity in clinical practice. Issue 6 (November 2016) - Menegatti-Chequini, Maria Cecilia; Gonçalves, Juliane P.B.; Leão, Frederico C.; Peres, Mario F. P.; Vallada, Homero
Abstract : Background: Although there is evidence of a relationship between religion/ spirituality and mental health, it remains unclear how Brazilian psychiatrists deal with the religion/spirituality of their patients. Aims: To explore whether Brazilian psychiatrists enquire about religion/spirituality in their practice and whether their own beliefs influence their work. Method: Four hundred and eighty-four Brazilian psychiatrists completed a cross-sectional survey on religion/spirituality and clinical practice. Results: Most psychiatrists had a religious affiliation (67.4%) but more than half of the 484 participants (55.5%) did not usually enquire about patients' religion/spirituality. The most common reasons for not assessing patients' religion/spirituality were 'being afraid of exceeding the role of a doctor' (30.2%) and 'lack of training' (22.3%). Conclusions: Very religious/spiritual psychiatrists were the most likely to ask about their patients' religion/spirituality. Training in how to deal with a patient's religiosity might help psychiatrists to develop better patient rapport and may contribute to the patient's quicker recovery.